Multi-Objective Optimization of Solvent-Free Microwave Extraction vs. Microwave Hydrodiffusion and Gravity for Amomum compactum Essential Oil - Variyana, Yeni; Rahma, Aulia Nabila; Mahfud, Mahfud (Pandawa Institute, 2026)
Amomum compactum essential oil, rich in 1,8-cineole (55–70%), is valued for its therapeutic and aromatic properties but suffers from low yield and thermal degradation in conventional extraction. This study compares and optimizes two green, solvent-free microwave-assisted methods—solvent-free microwave extraction (SFME) and microwave hydrodiffusion and gravity (MHG)—using Box–Behnken Design (BBD) under response surface methodology (RSM). Process variables included feed-to-distiller (F/D) ratio (0.10–0.20 g/mL), microwave power (150–450 W), and extraction time (60–90 min). SFME achieved the highest yield (5.25%) at 300 W, 0.15 g/mL, and 75 min, whereas MHG yielded 2.50% at 150 W, 0.10 g/mL, and 90 min, with superior 1,8-cineole recovery (59.65%) and linalool content (1.98%). Both methods reduced extraction time by 85–95% and energy use by over 90% compared with hydrodistillation, consuming only 0.004–0.006 kWh/g. SEM results confirmed extensive gland rupture (80–90%) and structural breakdown supporting enhanced mass transfer. These findings highlight SFME and MHG as sustainable, energy-efficient innovations aligning with SDGs 9, 12, and 13, advancing the circular bioeconomy and scalable green production of Amomum compactum essential oil.